Effect of the Root Extract of Fagara Zanthoxyloides on Blood Coagulation - Essien, E. M; Okogun, J. I (Thrombosis and Haemostasis, 1976)
The clot-promoting activity of the aqueous extract of Fagara zanthoxyloides Lam plant is described for the first time. It significantly shortened the PTT (K) of normal and factor VIII deficient plasma while it manifested no such action on factor IX-deficient plasma. This activity could be demonstrated in the residue of the lyophilized aqueous extract after its successive extraction with ether, chloroform and methanol. It could not be attributed to the purified fractions: Zanthoxylol or its modified form 3, 4-dihydro-2,2-dimethyl-2H-1 benzopyran-6-butyric acid (DBA), hesperidin, Fagaramide or the ether soluble fraction of the aqueous extract.